The head of department's handbook - Jones, Jeff.; Kirkham, Sue.; Jenkin, Masda (Bangalore : Heinemann educational, 1996)
This is a guide for every head or aspiring head of department that offers the practical help needed to organize your thoughts and develop a strategy for improvement. It is the complementary volume to "Managing a Department" and it offers advice and pro-formas to help produce a department development plan and policy documents, to audit resources and to prepare for inspection. The appendices include photocopiable resources such as scheme-of-work planning grids, administrative-task planners, student-referral records and INSET evaluation forms.
Keywords: v -- Great Britain